Circular RNA microarray expression profile and potential function of circDOCK1 in colorectal cancer - Zhang, Guojing; Wu, Xiaoyan; Fu, Hongmin; Sun, Daqing (Frontiers in Genetics, 2025)
IntroductionEndoscopic tissue biopsy combined with histopathology is the gold standard for the diagnosis of colorectal cancer (CRC); however, the invasive nature of this procedure hinders its acceptance by patients. Therefore, there exists a critical need to identify novel markers facilitating early CRC detection and prognosis. Circular RNAs (circRNAs) hold promise as novel clinical diagnostic markers. This study aimed to investigate the impact of circDOCK1 on CRC metastasis and prognosis as well as its underlying molecular mechanisms.MethodsWe explored circRNA expression profiles in four pairs of CRC tissues and adjacent non-carcinoma tissues via microarray analysis. After Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and circRNA–miRNA network analyses, circDOCK1 was chosen for further investigation. We evaluated its clinical relevance in 80 CRC tissue pairs and adjacent controls, correlating circDOCK1 expression with clinical characteristics. Follow-up data from patient telephone interviews were analyzed for survival outcomes. Transfection efficiency was confirmed via qRT-PCR in HCT116 and SW480 colon cells, and the effects of circDOCK1 on cell proliferation, migration, and invasion were assessed.ResultsMicroarray data revealed 149 significantly differentially expressed circRNAs, including 71 upregulated and 78 downregulated circRNAs, in CRC tissues. CircDOCK1 exhibited elevated expression in patients with CRC and emerged as an independent prognostic factor. Kaplan–Meier curve analysis suggested that circDOCK1 expression is an unfavorable prognostic factor in patients with CRC. In vivo experiments revealed that circDOCK1 overexpression enhanced the proliferation, migration, and invasion of CRC cells, with consistent results upon circDOCK1 downregulation.ConclusionThese data indicate that circDOCK1 may play a role in promoting the proliferation, migration, and invasion of CRC cells, suggesting its potential as a CRC biomarker.